Compreensões de professores de ciências da educação básica acerca de currículo: um estudo exploratório - Kreuz, Kelly Karine (2020)
Over the past twenty years, the history of Basic Education in Brazil can be characterized by public policies aimed at qualifying the teaching and learning processes in the classroom and teacher training. Policies that reach schools and directly impact the production of school curricula. Because of this, the investigation defined for the time being, emerges from the particular interest in finding answers about how teachers understand the school curriculum and the concern about the impact of this understanding on the quality of Brazilian Basic Education, especially with the process of teaching and learning Science. In this sense, it is sought, through this research, to analyze understandings of teachers of Basic Education about the construction of the school curriculum of science teaching in Brazil. When taking as object of the present study speeches of teachers of the area of Sciences of the Nature in effective exercise in the Basic Education. For the investigation process we used the category of recontextualization by hybridism proposed by Lopes (2005). The study is relevant to the Brazilian educational context as it contributes to the understanding of the interpretation process to which the official curricular documents and policies are submitted and expressed in the speeches of teachers through their curricular understandings. Especially, because it occurs in a school context and at a time when schools are discussing curriculum movements with the arrival of BNCC in schools. Still, the importance of carrying out research in the local context of UFFS / campus Cerro Largo is highlighted, considering that throughout the ten years of insertion of the university, several studies and projects of continuous formation of teachers of Science area have been carried out. Nature, in view of the area courses offered in this space. In the studies, results have been identified that qualify the teaching work and transform the teaching and learning processes in Sciences at the local and regional level. Thus, this study is presented, which is linked to line 1 of the Graduate Program in Science Teaching - PPGEC, and deals with a qualitative research carried out in two stages, the first being a bibliographic survey of the understandings of Basic Education teachers about the curriculum in Science teaching and an epistemological analysis of academic studies that deal with the category of recontextualization by hybridism, and, the second stage, an empirical research, carried out through a case study, with teachers in the area of Natural Sciences at a public school in the Missions region. Through the investigation process, we identified three emerging categories in the speeches analyzed: content-naive understanding of school curriculum, curriculum understanding from a content-critical perspective and school curriculum under a critical-reflexive understanding. In view of the identified categories, we show that curricular understanding from a content-critical perspective is more recurrent among science teachers working in Basic Education. In this sense, we build our defense that the speeches about the curriculum in Science teaching are recontextualized in Basic Education, which favors the construction of new understandings and contributes to qualify teachers' understanding more critically and reflexively.